Пространственный анализ парламентских выборов–2006 в Украине - Хинич, М.; Хмелько, В.; Клочко, М.; Ордешук, П. (Социология: теория, методы, маркетинг, 2008)
Following the parliamentary election of 2006 and the protracted negotiations there after, Ukraine witnessed the formation of a coalition that undermined many of the gains seemingly won by the Orange Revolution with the reemergence of Victor Yanukovich as its Prime Minister. A critical element of this reemergence was the defection of Aleksandr Moroz to Yanukovich’s Party of Regions, which, along with the Communists, formed a governing parliamentary coalition. Applying the methodology of spatial analysis of party positions to data from a nation-wide pre-election poll, we estimate the spatial positions of the leading parties and political personalities and as, on the basis of those estimates, whether Yanukovich’s governing coalition should be deemed “inevitable” as dictated by formal theories of coalition formation or whether it best be described as a blunder on the part of President Yushchenko and his Orange Coalition partners.